A methodology to surface aspects of organisational culture to facilitate lean implementation within SMEs. (14th December 2020) - Alkhoraif, Abdullah Abdulaziz; McLaughlin, Patrick
The purpose of this paper is to provide an instructional guidance on how to surface aspects of organisational culture (OC) that effect lean implementation within small and medium sized manufacturing organisation. This paper describes how grounded theory and action research can be used inside each other. The paper suggests to not only using a translation method to validate the result but to use also inter-rate reliability to increase the validity and reduce the subjectivity. The paper also demonstrates how different technique can help management research by including in a time effective way.